Solopreneur business - Rando, Joe; Ries, Carly (--For dummies., 2026)
"Create and run your one-person business with pro advice and strategic tools. Solopreneur Business For Dummies offers advice and tools to create, grow, and manage your business when you're going it alone. Unlike entrepreneurs, solopreneurs typically create their businesses to serve their lives--instead of trying to scale as much as possible. To thrive in this lifestyle, you'll need to understand the basics of business operations, financial management, sales, and marketing. You'll also need to learn how to do all these things without burning yourself out. This book has you covered in all those areas. You'll also learn how to create a support network that offers guidance, emotional support, and business opportunities. Set your business up for success with this no-nonsense Dummies guide." -- Amazon.